125 Increased plasma renin activity during wake in a repetitive sleep restriction protocol. (3rd May 2021) - Yang, Huan; Vazquez, Michael; Haack, Monika; Mullington, Janet
Abstract: Introduction: Insufficient sleep is associated with an increased risk of hypertension. It is well established that long-term BP regulation is modulated by the renin-angiotensin-aldosterone system (RAAS) and chronic kidney disease is a strong independent risk factor for development of cardiovascular disease. This study investigated the biomarkers of RAAS and renal function during repetitive exposures to controlled, experimental sleep restriction (SR). We hypothesized an upregulation of RAAS and increased markers of impaired renal function. Methods: Twenty-one healthy participants (11 women, average age 31±2 years) completed the 22-day in-hospital SR protocol: permitted 4h of sleep/night from 0300-0700 for 3 nights followed by a recovery sleep, repeated 4 times. Blood samples were collected and plasma renin activity (PRA) was assessed in the morning (7:05am) and in the evening before bedtime (22:45pm) at baseline, experimental days (3rd day of each of the 4 blocks), and recovery. Urinary albumin to creatinine ratio (ACR) was measured from 24-h urinary collection at baseline, first and fourth SR blocks. Estimated glomerulus filtration rate (eGFR) was calculated based on the serum cystatin C levels at baseline and last block of SR. Results: Percent change of evening PRA significantly increased during 4 blocks of SR and recovery (SR effect p=0.039), but not morning PRA (SR effect p=0.34). Specifically, evening PRA increased up to 98.4% in the first (p<0.01), 61.3% in the second (p=0.04) SR blocks, and 57.5% (p=0.05) in recovery. Urinary ACR showed no significant changes during first or fourth SR blocks (SR effect p=0.28). In addition, eGFR did not change in the fourth SR block compared to BL (paired t-test, p=0.27). Conclusion: We did not see increased markers of impaired renal function (ACR or eGFR). Rather, short-term repetitive exposures to SR significantly increased percent change of PRA measured before bedtime, and evening PRA did not return to BL level during recovery. Our results suggested that sleep deficiency may contribute to hypertension through upregulation of RAAS during wake time. Support (if any): SRSF (CDA to Huan Yang), NIH (R01HL106782 to Dr. Janet Mullington), Harvard Catalyst, Harvard Clinical and Translational Science Center (UL1TR001102).